The Existence and Perception of the Acehnese Towards the Myth of Bek Ria That - Humaira Anwar; Nurlayli Yanti; Zurahmi DE (Varied Knowledge Journal, 2026)
This study examines the existence and perception of the Acehnese people regarding the mythical phrase bek ria that, a prohibition against expressing excessive pleasure or joy. There is an urgent need to examine this research because of the gap between culture, which should be a source of welfare in life, and the meaning of this myth, which seems to prohibit happiness. This study aims to describe the existence and perception of the Acehnese people regarding the bek ria that myth. The approach used is a mixed methods approach with an ethnographic method, where data is collected through questionnaires, participatory observation, and in-depth interviews. The results of the study show that the myth of bek ria that is a sentence that has consequences for not being done by others. The existence of this myth in society is as a social heritage, a normal integration mechanism, and a collective representation. In addition, the study also shows a decline in understanding of the meaning of this myth among the younger generation in Aceh. This study also shows a shift in conception from magical beliefs to rationality. In addition, the religious discourse in this myth also makes it acceptable and perpetuated by society. It is very significant because it provides scientific contributions to social-cultural studies, psychology, and collective beliefs.